Dental aerosol: An insight - B Srishti Raj; Kharidhi Laxman Vandana (Wolters Kluwer Medknow Publications, 2021)
Aerosols are produced during dental procedures. An airborne route has long been said to be involved in transmission of infections. The recent COVID-19 has also been considered to spread by respiratory droplets or by the contact of contaminated surfaces. The nature of the dental practice hence poses threat to dentists, dental team, and patients owing to the accompanied aerosol-generating procedures. A thorough knowledge about the dental aerosol originated from various dental procedure needs to be present for suitable prevention of infectious hazards like the COVID-19. Hence, this review aims to throw light on literature related to mechanism and source of production, composition, microbial load, and potential diseases transmitted by dental aerosol.